2007
DOI: 10.1128/jb.00185-07
|View full text |Cite
|
Sign up to set email alerts
|

The Global Transcriptional Responses of Bacillus anthracis Sterne (34F 2 ) and a Δ sodA1 Mutant to Paraquat Reveal Metal Ion Homeostasis Imbalances during Endogenous Superoxide Stress

Abstract: Microarray analyses were conducted to evaluate the paraquat-induced global transcriptional response of Bacillus anthracis Sterne (34F 2 ) to varying levels of endogenous superoxide stress. Data revealed that the transcription of genes putatively involved in metal/ion transport, bacillibactin siderophore biosynthesis, the glyoxalase pathway, and oxidoreductase activity was perturbed most significantly. A B. anthracis mutant lacking the superoxide dismutase gene sodA1 (⌬sodA1) had transcriptional responses to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 83 publications
3
44
1
Order By: Relevance
“…3E, right) suggests that SodA2, predicted to be manganese dependent, is catalytically active when cofactored with iron. These results conflict with previous publications predicting that SodA1 and SodA2 were manganese-dependent enzymes (28,31), and the metal ion bound at the active site in published crystal structures of both enzymes was previously modeled as Mn 2ϩ (9).…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…3E, right) suggests that SodA2, predicted to be manganese dependent, is catalytically active when cofactored with iron. These results conflict with previous publications predicting that SodA1 and SodA2 were manganese-dependent enzymes (28,31), and the metal ion bound at the active site in published crystal structures of both enzymes was previously modeled as Mn 2ϩ (9).…”
Section: Resultscontrasting
confidence: 56%
“…3D, left). PMF using MALDI-TOF-MS identified this protein as SodA1 (ORF BA4499; see Table S1 in the supplemental material) (predicted MW ϭ 22,664; pI ϭ 5.31), one of four SOD enzymes encoded by the B. anthracis genome (31), which is predicted to utilize Mn 2ϩ as a cofactor (9,27,28). A number of unmatched peptides in this sample suggested that a mixture of proteins was present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…based on the available information about their survival mechanisms has yet to be undertaken (Christman et al, 1985;Inaoka et al, 1990;Farr and Kogoma, 1991;Givskov et al, 1994;Nitta et al, 2000;Sabra et al, 2002;Kabir et al, 2004;Passalacqua et al, 2006Passalacqua et al, , 2007Den Besten et al, 2009;Noor et al, 2009aNoor et al, , 2009bZuber, 2009;Pohl et al, 2011;Huillet et al, 2012;Murata et al, 2012;Den Besten et al, 2013;Nagamitsu et al, 2013). In relation to current studies on bacterial oxidative stress responses, the present study employed preliminary experiments to resolve the impact of increased concentration of the oxidant.…”
Section: Confirmative Demonstration Of E Coli and Pseudomonas Viabilmentioning
confidence: 99%